(untitled) (Świat Idei i Polityki, 2008)
This brief review of main problems contemporary politological profession, focusing on the criteria, which are applied in the process of professionalization political scientist. The arguments, which has been introduced, motivating the inadequacy of area of politological research to traditional ways delimitation of political science boundary. The dilemmas in this sphere, emphasize the need of wider discussion, or maybe the reconstruction of criteria,which defining politological profile of research. These questions, although have a theoretical nature, possess essential practical meaning. This concerns, the defining the formal requirements of scientific promotion decisions, and institutional competence recognition. The author tries to answer on such questions how: What criteria provide the qualification of disciplinary appurtenance of scientific work and which constitutes the disciplinary range of politological research? What feature of scientific property, should be taken for classification an explorers to definite discipline? What is more significant, formal set of education or problems, which they realy have undertaken in searches.